## 5^2/1.6 + 5^2/6.11 +…..+ 5^2/26.31(tính nhanh) x + 3/10 = 4/5 2/9 – 3.x = -4/3 (3/5 – x ) + 13/20 = 5/6 (2x – 1/2) =3/4

Question

5^2/1.6 + 5^2/6.11 +…..+ 5^2/26.31(tính nhanh)
x + 3/10 = 4/5
2/9 – 3.x = -4/3
(3/5 – x ) + 13/20 = 5/6
(2x – 1/2) =3/4

in progress 0
3 tuần 2021-07-09T22:18:37+00:00 2 Answers 2 views 0

1. 1. 5^(2)/1.6+5^(2)/6.11+…+5^(2)/26.31

=5.[(1-1/6)+(1/6-1/11)+…+(1/21-1/26)+(1/26-1/31)]

=5.(1-1/31)

=5.30/31

=150/31

2. x+3/10=4/5

<=>x=4/5-3/10

<=>x=1/2

Vậy x=1/2

3. 2/9-3.x=-4/3

<=>-3.x=-4/3-2/9

<=>-3.x=-14/9

<=>-3x=14/27

Vậy 14/27

4. (3/5-x)+13/20=5/6

<=>3/5-x=11/60

<=>x=11/60-3/5

<=>-5/12

Vậy -5/12

5. 2x-1/2=3/4

<=>2x=5/4

<=>x=5/8

Vậy x=5/8

#Study well

2. Đáp án:

Giải thích các bước giải:

a) 5. (5/(1. 6)+ 5/(6. 11)+…+ 5/(26. 31))

= 5. (1- 1/6+ 1/6- 1/11+…+ 5/26- 5/31)

= 5. (1- 1/31)

= 5. 30/31

= 150/31

b) x+ 3/10= 4/5

x= 4/5- 3/10

x= 8/10- 3/10

x= 5/10

x= 1/2

c) 2/9- 3. x= -4/3

3. x= 2/9- (-4/3)

3. x= 2/9- (-12/9)

3. x= 14/9

x= 14/9: 3

x= 14/9. 1/3

x= 14/27

(3/5- x)+ 13/20= 5/6

(3/5- x)= 5/6- 13/20

(3/5- x)= 50/60- 39/60

(3/5- x)= 11/60

x= 3/5- 11/60

x= 36/60- 11/60

x= 25/60

x= 5/12

2x- 1/2= 3/4

2x= 3/4+ 1/2

2x= 3/4+ 2/4

2x= 5/4

x= 5/4: 2

x= 5/4. 1/2

x= 5/8